Data Analysis for Gaining Insights on Customers’ Awareness About Quality of The Fish and Fishery Products - Stefan M. PETREA; Dragos Sebastian CRISTEA; Liliana MOGA; Alina MOGODAN; Ira A. SIMIONOV; Aurelia NICA; Sarina ROSENBERG; Victor CRISTEA (Communications of International Proceedings, 2020)
The research targets to get information regarding the fish and fishery products consumption, preference and the factors that influence the decision to buy, in association with the socio-economic characteristics of the consumers and to make an assessment of how the availability of information related to the traceability of fish-based products would influence the intention to buy these products in the future. A number of 12 parameters are considered for the analysis. Also, considering the data related to fish consumption, three time series algorithms were used. The exponential smoothing forecast method registered the highest accuracy. The subgroup analyses of socio-demographic characteristics reveal the emergence of new types of consumer preferences. When the geographical availability of fisheries is considered, the gradual increase in importance of the hypermarket becomes more obvious. In this context, the high dependence on the offer of hypermarkets raises the risk of an impoverished consumer choice in the near future. Education and product diversification are determinant factors for improving Romanian yearly fish consumption rate.
Keywords: Traceability; Fish Consumption; Fishery Sector; Time Series Algorithms.